2001
DOI: 10.1177/096369350101000404
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Behaviour of Polypropylene-Based Nanocomposites in the Melt State

Abstract: Nanoparticles of the standard pyrogenic Aerosil 1380 (Degussa) pregrafted by ã-irradiation with styrene were melt-compounded with the general purpose isotactic polypropylene (PP) homopolymer by a single-screw extruder. Storage G¢(w) and loss G²(w) shear moduli of the neat PP (PP-0) and of the nanocomposite with the filler volume content 4.68 % (PP-4.68) were treated to derive the relaxation times spectra h (t) using the NLREG computer program based on Tikhonovs method of non-linear regularisation. Drastic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…At higher frequencies, G'(ω) and G''(ω) started to diverge and to exhibit a frequency dependence (although much weaker than that for the pristine polymer). These data may be considered 8,9 as experimental evidence for the existence of a spatial network of filler particles coated with a polymer boundary layer in the lowfrequency range, and for its plastic yield at higher frequencies for sample 299D. As might have been expected, the viscoelastic behaviour of the sample 299E proved intermediate between those for two other nanocomposites.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…At higher frequencies, G'(ω) and G''(ω) started to diverge and to exhibit a frequency dependence (although much weaker than that for the pristine polymer). These data may be considered 8,9 as experimental evidence for the existence of a spatial network of filler particles coated with a polymer boundary layer in the lowfrequency range, and for its plastic yield at higher frequencies for sample 299D. As might have been expected, the viscoelastic behaviour of the sample 299E proved intermediate between those for two other nanocomposites.…”
Section: Resultssupporting
confidence: 58%
“…The processability of nanocomposites, however, can present some problems, in view of the extreme sensitivity of melt flow behaviour to the aspect ratio of clay nanoparticles 4 and to the quality of their dispersion (exfoliation) [4][5][6][7] . Moreover, viscoelastic studies of irradiation-grafted nano-inorganic particlefilled polypropylene composites in the melt state 8,9 revealed the onset of a plastic yield phenomenon for a nanocomposite with the filler volume content as low as 4.68% . This was regarded as experimental evidence for the shear-resistant, infinite cluster of nanoparticles coated with a polymer boundary interphase (BI) when the ratio of the mean thickness of the polymer interlayer between neighbouring nanoparticles, <L> , to the mean radius of gyration of a polymer coil, <R g > , approached the "critical" value, <L>/<R g > ≈ 1.…”
Section: Introductionmentioning
confidence: 99%
“…General purpose isotactic polypropylene homopolymer (grade F 401, melt flow index MFI ¼ 8:5 g=10 minÞ (8,9) was used as a reference sample (hereafter PRIVALKO ET AL. 540 referred to as PP-0).…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, polymer-clay nanocomposites should have nothing special compared to other filled polymers 4 , except a much smaller particle size (hence, a much larger specific area) and a much lower degree of particle agglomeration. In fact, our previous studies of polypropylene/organosilica PNC [5][6][7] highlighted the structural significance of the ratio of the mean thickness of the polymer interlayer between neighbouring nanoparticles, <L>, to the mean radius of gyration of a polymer coil, <R g >. In the range of low filler loadings characterized by large scaled distances, <L>/<R g > ≥ 1, all PNC in the melt state behaved as Newtonian liquids in which the self-diffusion of macromolecular coils was, however, slowed down.…”
Section: Introductionmentioning
confidence: 99%
“…In the range of low filler loadings characterized by large scaled distances, <L>/<R g > ≥ 1, all PNC in the melt state behaved as Newtonian liquids in which the self-diffusion of macromolecular coils was, however, slowed down. The onset of a plastic yield phenomenon for a sample with filler volume content as low as 4.68% was regarded as experimental evidence for the shearresistant, infinite cluster of nanoparticles coated with a polymer boundary interphase when the scaled distance approached the "critical" value, <L>/<R g > ≤ 1 5,6 . Stretching calorimetry studies of these PNC in the solid state 7 has revealed a considerable excess of Young's moduli concomitant to the deficit of thermal expansivities, and limiting strains for elastic behavior and breaking strains compared to reasonable theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%